KESULITAN SISWA DALAM MENYELESAIKAN MASALAH PENJUMLAHAN DAN PENGURANGAN DENGAN METODE JARIMATIKA DAN PEMBERIAN SCAFFOLDINGNYA - Siti Daiyatul Hamidah; Ali Shodikin; Siti Amiroch (INSPIRAMATIKA, 2019)
This study aims to determine the difficulty and the provision of appropriate scaffolding used by students in solving addition and subtraction problems with the Jarimatic method. As for the difficulties of students analyzed in the form of fact errors, operational errors, and principle errors as well as the form of scaffolding conducted, namely explaining, reviewing, and restructuring. The subjects in this study were 32 first grade students at SDN Sumurber. The instruments in the study were written tests and interviews. The results of this study are (1) errors of fact students still have difficulty in operating fingers, (2) errors of operation where there are still many students who still have difficulty in calculating addition and subtraction operations, (3) and principle errors occur in some more students likes to count with chimera and haste. Scafolding provided includes explaining, reviewing, and restructuring.